The search of new biologically active compounds with antibacterial and antifungal activity among 1,2,4-triazole-3-thiol derivatives with the remnants of thiophene - V. O. Salionov; O. I. Panasenko; Ye. G. Knysh; O. M. Kamyshnyi (Zaporozhye State Medical University, 2017)
The resistance of microorganisms to antimicrobial and antifungal drugs is still an actual issue in the modern world. Therefore, one of the possible ways to solve this problem is the creation of new drugs. Derivatives of 1,2,4-triazole are interesting in this aspect. In addition a lot of information is published in the scientific literature on the prospects of further research but research data on antimicrobial and antifungal action of 4-R-5-(5-bromthiophen-2-yl)-1,2,4-triazole-3-thiols and 4-R-methylidenamino-5-(thiophen-2-yl)-1,2,4-triazole-3-thiols is missing. The aim of the work. The study of antibacterial and antifungal activity of new 4-R-5-(5-bromthiophen-2-yl)-1,2,4-triazole-3-thiols and 4-R-methylidenamino-5-(thiophen-2-yl)-1,2,4-triazole-3-thiols and establishing the "structure-action" dependence. Materials and methods. For the studied compounds we prepared series of two-fold serial dilutions in Mueller-Hinton broth in a volume of 1 ml using an initial concentration of substance 1 mg/ml. Then in each tube we added 0,1 ml of microbial suspension (106 microbial cells/ml). As a standard test strains we used: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans. All test strains were obtained from the bacteriological laboratory of the State Institution "Zaporizhzhya Regional Laboratory Center for State Sanitary and Epidemiological Service of Ukraine." As a solvent of compounds we used dimethylsulfoxide (99,80%). Additionally a control culture media and solvent were held according to conventional methods. As comparison drugs we used Chlorhexidine-Zdorov'ya® (Ukraine) and Nistatin-Zdorov'ya® (Ukraine). Results. Analyzing the obtained data of antimicrobial and antifungal activity it was revealed that the compounds demonstrated selective antimicrobial action. Thus, 4-amino-5-(5-bromthiophen-2-yl)-1,2,4-triazole-3-thiol showed the highest antimicrobial effect against strains of Staphylococcus aureus exceeding Chlorhexidine and antifungal effect against strains of Candida albicans approaching to comparison drug Nistatin. At the row of 4-R-methylidenamino-5-(thiophene-2-yl)-1,2,4-triazole-3-thiols clear patterns were not found. 4-[(5-nitrofuran-2-yl)methylidenamino]-5-(thiophene-2-yl)-1,2,4-triazol-3-thiol is interesting because of its higher antimicrobial effect than Chlorhexidine against the strains of Escherichia coli and Staphylococcus aureus. For all other compounds minor antimicrobial effect and no antifungal activity were noted. Conclusions. Antimicrobial and antifungal activity of 13 new 1,2,4-triazole-3-thiol derivatives were first time studied. Compounds which showed the highest antimicrobial activity can be used in further biological tests.